Combination treatment with erlotinib and ampelopsin overcomes erlotinib resistance in NSCLC cells via the Nox2-ROS-Bim pathway. (April 2017) - Hong, Seung-Woo; Park, Nam-Sook; Noh, Min Hye; Shim, Ju A; Ahn, Byul-Nim; Kim, Yeong Seok; Kim, Daejin; Lee, Hyun-Kyung; Hur, Dae Young
Highlights: Addition of ampelopsin to erlotinib dramatically induces apoptosis in erlotinib-resistant NSCLC cells. Combinational treatment with erlotinib and ampelopsin activates apoptosis through NOX2-dependent ROS-Bim signaling pathway. A combination strategy with erlotinib and ampelopsin could be used to overcome resistance to erlotinib in NSCLC. Abstract: Objectives: Erlotinib, a tyrosine kinase inhibitor (TKI) of epidermal growth factor receptor (EGFR), has been shown to have a dramatic effect in non-small cell lung cancer (NSCLC) patients with EGFR mutation. However, the presence of primary resistance or acquired resistance to EGFR-TKI is the most common reason for switching to other anti-cancer agents. Even though there are newer agents that have activity in the presence of the T790 M mutation, identification of potential agents that could overcome resistance to EGFR-TKI is still needed for the treatment of NSCLC patients. Materials and methods: In this study, we used erlotinib-resistant NSCLC cell lines to investigate the effects of combination treatment with erlotinib and ampelopsin. After treatment with either single or combination, cell viability and cell death were determined with WST-1 assay, trypan blue exclusion method, colony forming assay, annexin-V staining assay and western blot assay. The content of ROS was evaluated by FACS analysis using H2 DCF-staining method. To determine the effect of Nox2 and Bim on the combined treatment with erlotinib and ampelopsin-induced cell death, we transfected with Nox2 or Bim specific siRNA and performed with western blot assay for evaluation of its expression. Results: Combined treatment with erlotinib and ampelopsin at non-cytotoxic concentrations significantly induced caspase-dependent cell death in erlotinib-resistant NSCLC cells. Furthermore, cell death resulted in the accumulation of reactive oxygen species (ROS) through upregulation of nicotinamide adenine dinucleotide phosphate oxidase 2 (Nox2) expression, a direct source of ROS. The expression level of Bim increased with combination treatment, but not with either treatment alone. Conclusion: Here in this study, we demonstrate that the combination of erlotinib and ampelopsin induces cell death via the Nox2-ROS-Bim pathway, and ampelopsin could be used as a novel anti-cancer agent combined with EGFR-TKI to overcome resistance to erlotinib in EGFR-mutant NSCLC.